2020
DOI: 10.3389/fendo.2020.00590
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Exosomal MiRNA-4534 as a Novel Diagnostic Biomarker for Diabetic Kidney Disease

Abstract: Urinary exosomal miRNAs can reflect the physiological and possibly pathophysiological state of cells lining the kidney and participate in the regulation of transcription and translation of proteins, which are playing an important role in the pathogenesis of diabetic kidney disease. In the present study, urine was collected from DM and DKD patients with a duration more than 10 years and urinary exosomal miRNA profiling was conducted in urinary exosomes obtained from three patients with type 2 diabetes (DM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…In addition, the results revealed that expressed of miR-5007-3p was upreglated in patients with positive lymphatic metastasis of primary gastric tumors [ 36 ]. In addition, another experiment by RT-qPCR indicated that the relative expression level of miR-5007-3p was significantly upregulated in the diabetic kidney disease group compared to type 2 diabetes group [ 37 ]. However, these researches did not examine miR-5007-3p specific cellular functions, and miR-5007-3p expression in HCC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results revealed that expressed of miR-5007-3p was upreglated in patients with positive lymphatic metastasis of primary gastric tumors [ 36 ]. In addition, another experiment by RT-qPCR indicated that the relative expression level of miR-5007-3p was significantly upregulated in the diabetic kidney disease group compared to type 2 diabetes group [ 37 ]. However, these researches did not examine miR-5007-3p specific cellular functions, and miR-5007-3p expression in HCC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results revealed that expressed of miR-5007-3p was upreglated in patients with positive lymphatic metastasis of primary gastric tumors [33]. In addition, another experiment by RT-qPCR indicated that the relative expression level of miR-5007-3p was signi cantly upregulation in the Diabetic kidney disease group compared to type 2 diabetes group [34]. However, these researches did not examine miR-5007-3p speci c cellular functions, and miR-5007-3p expression in HCC is unclear.…”
Section: Discussionmentioning
confidence: 91%
“…hsa-miR-4279 is expressed in urinary extracellular vesicles of Diabetic patients with macroalbumin, while hsa-miR-3941 is linked with islet immunity [ 92 94 ]. hsa-miR-5088-5p is upregulated in urine in the case of Diabetic Kidney disease [ 95 ]. hsa-miR-4747-5p is downregulated in human aortic vascular smooth muscle cells with high glucose-induced calcification/senescence [ 96 ].…”
Section: Discussionmentioning
confidence: 99%